Giant Primary Scrotal Lipoma: A Rare Entity with Diagnostic Pitfalls. (5th November 2020) - Vignot, Louis; Saad, Elie; Peyromaure, Michael; Barry Delongchamps, Nicolas
Abstract : Primary scrotal lipomas are rare. We describe the case of a 47-year-old male with a giant scrotal lipoma who underwent a surgical excision. We report the clinical and radiological approach as well as the treatment of this atypical benign tumor.